Analisis Putusan Mahkamah Konstitusi No: 90/Puu-Xxi/2023 Terkait Batas Usia Calon Presiden Dan Wakil Presiden Indonesia - Manurung, Mangaraja; Azmi, Fahri (Peneliti.net, 2025)
The KPU is a national election organizer that has a constant and independent character. Letter b Article 13 of Law No. 7 of 2017 concerning Elections reports that the KPU has the authority to establish KPU regulations at all stages of the election. This is done to ensure that all stages of selection occur. Place within a deadline. In elections where a dual candidate for president and vice president is proposed by a political party or a combination of several political parties participating in the election, there are various provisions that the political party can comply with in the proposal before the election begins. One of the parties or a combination of political parties participating in the election is said to be the age limit for nominating presidential and vice presidential candidates. In this legal research, normative legal research methods are used and the problem approach used is the statutory approach. This legal research uses primary legal materials, namely: Legislation. Secondary legal materials, namely: law books. Tertiary legal materials, namely: non-legal books.The reason for the Petitioner and Under the Law to submit Application No. 90/PUU-XXI/2023 concerning the Age Limit for Presidential and Vice Presidential Candidates is that there is discrimination that the applicant said is related to the age limit. For the applicant, this is due to the myth that is growing among the community that elderly people are always thought to be capable/able to be included as Regent. The legal evaluation of the Constitutional Court judges in their decision No. 90/PUU-XXI/2023 concerning the age limit for presidential and vice-presidential candidates is that the Court's consideration of the Petitioner's issue regarding Article 169 letter (q) of Law No. 7 of 2017 is